THE CROSS-SECTORAL TECHNOLOGICAL INTERDEPENDENCIES OF CENTRAL AND EASTERN EUROPE IN THE ERA OF INDUSTRY 4.0 AND CHINESE DIGITAL SILK ROAD - Cieślik, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The article aims to assess the flows of value added in the servicification of manufacturing within the two most critical value-added providers for Central and Eastern Europe (CEE): Germany and China in the era of Industry 4.0 and the Digital Silk Road (DSR). Methods: The input-output model for the decomposition of gross exports was applied to evaluate the cross-sectoral links between analyzed economies. Results: The CEE economies are increasingly dependent on high-quality services from Germany and China for their manufacturing, while analogous flows from CEE to Germany and China are decreasing or remaining stable. German manufacturing is starting to depend more on Chinese services’ value-added in advanced sectors. There was no direct trade-off between pairs of economies, but a decrease in German value-added flows to China led to a significantly larger increase in Chinese value-added in German manufacturing. Conclusions: Bearing in mind the limitations of the study, the deepened imbalance in value-added flows between economies was proved. Moreover, the study proved the effectiveness of China’s Industry 4.0 and DSR in terms of enhancing the sophistication of Chinese value-added exports and making key economies reliant on this value-added